(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, A highly compact (volume of only 7 x 7x1.6mm3) crown slot patch antenna, operating at 28GHz (5G mobile applications) and 34GHz (higher satellite band application ) is presented. A structure of antenna is integrated with heptagon radiator and crown shaped slot on the radiating element. The proposed configuration has The antenna has S11 <-10dB bandwidth of 4.39GHz at 28 GHz and 2.36GHz at 34GHz.The obtained bandwidth can easily satisfy the requirement of millimeter 5G and higher satellite band.Which is highly compact size, overall radiation efficiency, good gain, table radiation pattern obtained at targeted 5G application.